INFLAMMATION - P.F. Litvitsky (Вопросы современной педиатрии, 2006)
In the article the characteristic of ethiology and key parts of pathogenesis of inflammation is given; modern data on the role of adhesive molecules, active forms of oxygen, lipoperoxidation processes, cytokines and other mediators in the development of acute and chronic inflammation are analyzed; the principles of its treatment are substantiated.Key words: inflammation, phlogogenic agents, alteration, adhesion molecules.